Informed adaptation: Ethical considerations for adaptation researchers and decision-makers. (May 2015) - Lacey, Justine; Howden, S. Mark; Cvitanovic, Christopher; Dowd, Anne-Maree
Highlights: There is increased focus on how to support decision-makers adapt to climate change. Closer examination of the roles and responsibilities of researchers is required. The distinction between research and operational aspects of adaptation is critical. Lessons are drawn from experience in the medical and other sectors. We examine professional ethics and suggest protocols for adaptation researchers. Abstract: Given the significant and irreversible impacts of climate change on communities and the environment, there is increasing focus on how to best support decision-makers to adapt to climate change. Generally, the research on this tends to focus on assessing how decision-makers navigate elements of risk and uncertainty in deciding to what extent they should adapt their practice if at all, however, scientific researchers also have a key role to play in supporting these adaptation decisions. Given the applied nature of adaptation research, we argue that an examination of the roles and responsibilities of researchers is critical to understanding the ethical aspects of professional research practice in the adaptation context. This includes identifying how researchers can best support adaptation, and exploring the responsibilities that researchers have, not only to decision-makers but also to the broader membership of the adaptation community. In this paper we examine the ethical responsibility of researchers in supporting decision-makers to adapt to climate change, using agricultural producers as a case-study and focal group. Specifically, in undertaking this examination of risk and responsibility in adaptation research and decision-making, we use the lens of professional ethics to outline how research might better contribute to informed adaptation. We argue that clarifying the distinction between the research and operational aspects of agricultural adaptation, and how the interface between the two is disclosed, is critical. We also describe and explore the ethical considerations of researchers associated with stakeholder engagement in relation to adaptation science, and identify the need for institutional innovation for more effective engagement. In doing so, we seek to demonstrate how ethical research practice can support greater alignment of science and public values in agricultural adaptation, thus increasing the likely success of decisions.